Guidelines for Best Practice in the Audiological Management of Adults with Severe and Profound Hearing Loss - Turton, Laura (Semin Hear, 2020)
Individuals with severe to profound hearing loss are likely to present with complex listening needs that require evidence-based solutions. This document is intended to inform the practice of hearing care professionals who are involved in the audiological management of adults with a severe to profound degree of hearing loss and will highlight the special considerations and practices required to optimize outcomes for these individuals.